Strategi Pengembangan Usaha Pada Optik Damar Melalui Pendekatan Analisis Swot Dan Business Model Canvas - Wulandari, Asti; Herlinawati, Erna (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to formulate a business development strategy for Optik Damar using SWOT analysis and the Business Model Canvas (BMC) approach. The research was conducted using a descriptive qualitative method, which included observation and interviews as data collection techniques. The results show that the main strengths of Optik Damar include product quality and customer loyalty, while its weakness lies in dependence on a single supplier. Opportunities that can be leveraged include increasing public awareness of eye health and the potential of online markets, whereas the main threats come from intense competition and changing consumer trends. The analysis results led to recommendations for a new Business Model Canvas to enhance competitiveness and growth potential. The suggested strategies include diversifying suppliers, implementing technology-based innovations, and optimizing digital marketing. The implementation of these strategies is expected to support the sustainability of Optik Damar's business in the future.